2007
DOI: 10.1002/acp.1377
|View full text |Cite
|
Sign up to set email alerts
|

The effects of disappointment on hindsight bias for real‐world outcomes

Abstract: Examined the effects of motivated processing on hindsight bias. One hundred fifty three college students estimated and later recalled the likelihood that 30 self-relevant events would occur during the next 2 months. Multi-level modelling was used to determine the (within-subject) effects of expectations, event valence and event controllability on hindsight bias and the extent to which these effects were moderated by participants' need for cognition (NFC) scores (between-subjects). For events that actually occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 37 publications
4
27
0
Order By: Relevance
“…This suggests that the opposite effects observed in previous studies were probably driven by the different hindsight components, rather than by any differences in the controllability of the event outcomes in question. Supporting this interpretation, Pezzo and Beckstead (2008) found no effect of event controllability on their foreseeability-related measure of hindsight bias.…”
Section: Scenariossupporting
confidence: 62%
See 3 more Smart Citations
“…This suggests that the opposite effects observed in previous studies were probably driven by the different hindsight components, rather than by any differences in the controllability of the event outcomes in question. Supporting this interpretation, Pezzo and Beckstead (2008) found no effect of event controllability on their foreseeability-related measure of hindsight bias.…”
Section: Scenariossupporting
confidence: 62%
“…Instead of believing in hindsight that they knew this all along, as a strictly cognitive view of hindsight bias would hold (unless the outcome is surprising-in which case, hindsight bias can be attenuated or even reversed; see Müller & Stahlberg, 2007, for an overview), quite a number of studies have shown that hindsight is reduced and often eliminated under such conditions (Louie, 1999(Louie, , 2005Louie, Curren, & Harich, 2000;Mark, Boburka, Eyssell, Cohen, & Mellor, 2003;Mark & Mellor, 1991;Pezzo & Beckstead, 2008). Importantly, this holds even if any possibly confounding influence of surprise is controlled for (Louie, 1999).…”
Section: Controllability and Hindsight Components: Understanding Oppomentioning
confidence: 97%
See 2 more Smart Citations
“…Such phenomenon is studied in other fields like auditing, businesses ethics, court decisions, and many others, and its impact in different situation. The evidence can be found the studies of (Roese & Vohs, 2010;Pezzo & Beckstead, 2008;Mueller & Stahlberg, 2007;Nestler & Egloff, 2009;Lowe & Reckers, 2000;Anderson, Jennings, Lowe, & Reckers, 1997;Gilibert & Banovic, 2009;Wasieleski, Whatley, & Murphy, 2009;Annunziata, 2009;Sligo & Stirton, 1998;Wallace, Chang, Carroll, & Grace, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%